2013
DOI: 10.2116/analsci.29.991
|View full text |Cite
|
Sign up to set email alerts
|

A Cytosine-rich DNA Decorated Gold Nanoparticles Surface Enhanced Raman-Scattering Platform for Sensitive and Selective Detection of Silver Ions

Abstract: In this work, we developed a label-free, homogeneous surface-enhanced Raman-scattering (SERS) platform for the rapid, simple and sensitive detection of Ag + by using the unmodified gold nanoparticles (AuNPs). It utilizes the different absorption properties of single-strand DNA (ssDNA) and double-strand DNA (dsDNA) on citrate-coated AuNPs and specific interactions between Ag + and cytosine-cytosine pairs. In the presence of Ag + , the structure of ssDNA containing rich cytosine will form a duplex, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…A colorimetric and surface-enhanced Raman scattering dual-signal sensor for Hg 2+ ions based on bismuthiol II-capped gold nanoparticles, has been proposed by Duan et al [257]. Such strategies have been applied for the detection of Pb 2+ [258,259] Zn 2+ [260], Ni 2+ [261], Cu 2+ [262][263][264], Cr 3+ [265], Co 2+ [263], As 3+ [266] and Ag + [259,267]. Ly and Joo [268] proposed a SERS sensor for Hg 2+ ions based on the selective changes in the Raman signals of poly-L-lysine at 458 and 1115 cm -1 , in contrast with other ions (Cr 3+ , Pb 2+ , Mn 2+ , Zn 2+ , Co 2+ , Ni 2+ , Cd 2+ , Fe 2+ , Na + , Ca 2+ , Mg 2+ , Cu 2+ , NH 4 + and Fe 3+ ).…”
Section: Ancillary Complexing Agentsmentioning
confidence: 99%
“…A colorimetric and surface-enhanced Raman scattering dual-signal sensor for Hg 2+ ions based on bismuthiol II-capped gold nanoparticles, has been proposed by Duan et al [257]. Such strategies have been applied for the detection of Pb 2+ [258,259] Zn 2+ [260], Ni 2+ [261], Cu 2+ [262][263][264], Cr 3+ [265], Co 2+ [263], As 3+ [266] and Ag + [259,267]. Ly and Joo [268] proposed a SERS sensor for Hg 2+ ions based on the selective changes in the Raman signals of poly-L-lysine at 458 and 1115 cm -1 , in contrast with other ions (Cr 3+ , Pb 2+ , Mn 2+ , Zn 2+ , Co 2+ , Ni 2+ , Cd 2+ , Fe 2+ , Na + , Ca 2+ , Mg 2+ , Cu 2+ , NH 4 + and Fe 3+ ).…”
Section: Ancillary Complexing Agentsmentioning
confidence: 99%
“…143 In addition, the HRP-mimicking DNAzyme can be used for the development of colorimetric sensors for Ag + assay. [144][145][146] The combination of C-Ag + -C coordination chemistry with dual polarization interferometry (DPI), 147 electrochemical assay, 148 Raman/Rayleigh scattering, 149,150 SPR light-scattering, 151 and phosphorescence 152 can be used to construct a variety of sensors for Ag + assay. The typical DPI-based sensor is developed by the immobilization of C-rich DNAs on the surface of sensing chips.…”
Section: Detection Of Silver Ions (Ag + )mentioning
confidence: 99%
“…[11][12][13][14] Formation of this stable complex has allowed the design of a number of analytical methods for Ag þ determination. [15][16][17][18][19][20] Detailed structural studies of cytosine-Ag þ complexes have also been reported. 21,22 The interaction of cytosine tautomers with the nanoparticle of all group 11 elements has been analyzed in details.…”
Section: Introductionmentioning
confidence: 99%